2009
DOI: 10.2319/030108-124.1
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Morphology in Prematurely Born Children

Abstract: Objective: To test the null hypothesis that there is no difference between the craniofacial morphology of prematurely born children and that of matched full-term born controls. Materials and Methods: White children 8 to 10 years of age, born at the University Hospitals of Lund and Malmö and living in the same part of Sweden, were included. One group consisted of 36 very preterm children, born during gestational weeks 29 to 32; the other group included 36 extremely preterm children, who were born before the 29t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 15 publications
2
22
0
2
Order By: Relevance
“…The study from 2009 with the same study material as this study found a significantly shorter anterior cranial base and a less convex skeletal profile among EPT compared to full-term children. Additionally, EPT and VPT children had significantly shorter maxillary lengths compared to full-term children [5].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The study from 2009 with the same study material as this study found a significantly shorter anterior cranial base and a less convex skeletal profile among EPT compared to full-term children. Additionally, EPT and VPT children had significantly shorter maxillary lengths compared to full-term children [5].…”
Section: Discussionmentioning
confidence: 88%
“…Disturbances in this process may result in a change in the size and shape of the craniofacial complex [24]. Premature birth has been shown to affect the morphology of the craniofacial complex [5]. The Table 4 Dental maturity score within the groups extremely preterm (EPT), very preterm (VPT), and full-term (FT), as calculated from the 5 observers' assessments of 7 left mandibular teeth (teeth 31-37) according to the method of Demirijan et al [15] Mean dental maturity score (SD) formation of tooth 37 is initiated during the second or third year of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a recent investigation concluded that the prevalence of malocclusion traits and the professionally assessed need of orthodontic treatment were greater in a group of preterm children than in a control group of full-term children [11]. In addition, a number of craniofacial parameters differed significantly between the preterm and full-term born control children [12].…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, formerly intubated neonates are more often affected by malocclusion traits and require more orthodontic treatment for growth modification [2,3]. Also, several craniofacial parametric differences exist between formerly mature and premature neonates especially in comparison to extremely premature groups (GA of 29-32 wks) [4]. At the minute trends to early surfactant administration and nasal continuous positive airway pressure (NCPAP) may change the minute.…”
mentioning
confidence: 99%